2021
DOI: 10.1002/solr.202100809
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous CdO‐In2O3 Electrode for Perovskite‐Based Bifacial and Tandem Photovoltaic Technologies with High Energy Production

Abstract: Energy production of perovskite‐based photovoltaic (PV) technology can be increased not only by improving device efficiency of perovskite solar cells (PVSCs) but also by innovative concepts such as bifacial and tandem configurations which require low‐damage and highly transparent top electrodes. Herein, an amorphous CdO‐In2O3 alloy film with high transparency and low resistivity and its application in a bifacial PVSC and a perovskite/Si 4T tandem solar cell are reported. Due to the high optical transmittance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that Ag nanowires, metal mesh, and carbon-based materials, such as carbon nanotubes and graphene, show better mechanical stability than crystalline ITO, but the corresponding flexible PSCs exhibit lower device performance. A recent work shows that amorphous Cd-doped indium oxides with improved mechanical, electrical, and optical properties can effectively replace ITO as the transparent electrode for flexible PSCs, which exhibit very decent efficiency and stability [26]. Such development may pave the way for the development of new transparent conducting oxide films that are more suitable for flexible electronic applications, including flexible PSCs.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…It has been demonstrated that Ag nanowires, metal mesh, and carbon-based materials, such as carbon nanotubes and graphene, show better mechanical stability than crystalline ITO, but the corresponding flexible PSCs exhibit lower device performance. A recent work shows that amorphous Cd-doped indium oxides with improved mechanical, electrical, and optical properties can effectively replace ITO as the transparent electrode for flexible PSCs, which exhibit very decent efficiency and stability [26]. Such development may pave the way for the development of new transparent conducting oxide films that are more suitable for flexible electronic applications, including flexible PSCs.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%